2020
DOI: 10.3390/su12198141
|View full text |Cite
|
Sign up to set email alerts
|

Memory for Social Sustainability: Recalling Cultural Memories in Zanqit Alsitat Historical Street Market, Alexandria, Egypt

Abstract: Historic urban landscapes (HULs) are composed of layers of imbedded tangible and intangible features such as cultural memories. As the collective memories of city inhabitants, cultural memories can affect elements of social sustainability such as health, well-being, community identity, place perception and social engagement. Utilising the popular Zanqit Alsitat (also known as ‘Zanket el-Setat’ or ‘Zane’t El-Settat’), the only remaining historical street market in Alexandria, Northern Egypt, this research propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Moreover, we addressed the place and value of cultural memory within urban management and sustainable development more widely. Our study of the Zanqit Alsitat suq demonstrated a theoretical model derived from our empirical research showing how the formation of place identity, sense of place, and civic pride, which foster QoL, are the drivers of social sustainability and can be achieved by reproducing the cultural memories of HULs (Hussein et al 2020c). Taken together, the discussions and conclusions presented in this series of articles examine the question of how important the inclusion of cultural memory is to psychosocial well-being in HUL urban conservation.…”
Section: Formulating Conclusion/construction Of Theory (Third Phase)mentioning
confidence: 63%
See 1 more Smart Citation
“…Moreover, we addressed the place and value of cultural memory within urban management and sustainable development more widely. Our study of the Zanqit Alsitat suq demonstrated a theoretical model derived from our empirical research showing how the formation of place identity, sense of place, and civic pride, which foster QoL, are the drivers of social sustainability and can be achieved by reproducing the cultural memories of HULs (Hussein et al 2020c). Taken together, the discussions and conclusions presented in this series of articles examine the question of how important the inclusion of cultural memory is to psychosocial well-being in HUL urban conservation.…”
Section: Formulating Conclusion/construction Of Theory (Third Phase)mentioning
confidence: 63%
“…To do this, the paper refers to case studies previously conducted at three sites in Alexandria, Egypt, in the Orabi Square, Masrah Al Salam context and Zanqit Alsitat market. Each of these places have been the subject of published research papers (Hussein et al 2020a(Hussein et al , 2020b(Hussein et al , 2020c that have developed GT to advantage in analysis. This paper uses these case studies as a ground for the discussion of GT as an approach for exploring the effect of cultural memory on psychosocial well-being in historic urban landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…Such spaces also aim to achieve social integration and acceptance as an alternative to exclusion and preference [81]. Urban resilience should improve people's well-being by creating inclusive urban public spaces where people have more positive experiences, a stronger sense of place, and a higher quality of civic pride [82,83].…”
Section: Community Well-beingmentioning
confidence: 99%
“…According to Hussein et al (2020), cultural memory forms the identity of the place and the sense of place, which form the attachment to the community, enhances psychological well-being (quality of life), and contributes to social sustainability.…”
Section: Knowledge From the Inside Of Social Memorymentioning
confidence: 99%